La presencia del cabello como construcción simbólica de la identidad femenina de caral mediante la acuarela - Jimenez Gomez, Karina Noemi (2024)
The main objective of this research is to expose the presence of hair as a symbolic construction of the female identity of Caral through watercolor, figuratively representing the empowered woman. The specific objectives are about defining the presence of hair and the social code through watercolor, as well as describing the relationship between the interpretation of hair and the empowerment of today’s women through watercolor. The materials to be used are liquid watercolors, tubes, watercolor colors, masking liquid, large, medium and small brushes. Everything is being made on 300 gr cardboard. 105 cm. x 57cm. The methodology is qualitative, this research is non-experimental-observational, which is reflected through the plastic work, in three watercolors, in the art nouveau style. The work is being elaborated and so far there is a significant progress of 60%, among the techniques used to achieve the representation of the aesthetics of the hair and the female body are being used: the gradient gouache technique on wet-dry cardboard; also, the techniques of dripping, color lifting, reserving the paper with a masking liquid and, finally, to generate textures for the backgrounds, sodium chloride is used. It is intended to evoke feminine power through these figures associated with food, textile production, thaumaturgy and reproduction.